Kontekstualisasi Keabsahan Nikah Sirri Pendekatan Hermeneutika Abdullah Saeed - Fikri Muh Ansor; Achmad Nursobah; Arifuat Marzuki (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Indonesia, as a country with a Muslim-majority population, applies a legal system that integrates both religious and state law, including in matters of marriage. However, the practice of nikah sirri, a marriage that is religiously valid but not officially registered by the state, remains widespread and raises various legal and social issues, particularly affecting women and children. This study aims to analyze the validity of nikah sirri through Abdullah Saeed’s hermeneutical approach from the perspective of maqāshid syarī‘ah. The method employed is a library research approach by examining Qur’anic and Hadith texts related to marriage and reviewing Abdullah Saeed’s contextual interpretation. The findings reveal that marriage registration is not merely an administrative formality but a legal protection mechanism aligned with the Islamic principle of public welfare (maslahah). By applying Saeed’s five levels of value hierarchy, obligatory, fundamental, protective, implementational, and instructional, it can be understood that marriage registration is an essential effort to safeguard human rights and prevent social and legal harm. Abdullah Saeed’s contextual approach emphasizes that Islamic law is dynamic and adaptive to the changing times; therefore, marriage registration can be viewed as an actualization of maqāshid syarī‘ah values in the context of modern Indonesia.